2011
DOI: 10.3109/02688697.2011.595847
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of a symptomatic synovial cyst of the lumbar spine

Abstract: We present a case of spontaneous resolution of a lumbar intraspinal synovial cyst. We discuss the management options, including conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The nonsurgical management consists of analgesics, physiotherapy, bracing, facet injection, and cyst aspiration [5]. Many studies have reported cases of spontaneous resolution of facet cyst with conservative treatment with complete remission of clinical and radiological findings [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonsurgical management consists of analgesics, physiotherapy, bracing, facet injection, and cyst aspiration [5]. Many studies have reported cases of spontaneous resolution of facet cyst with conservative treatment with complete remission of clinical and radiological findings [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The fluoroscopic or CT-guided direct lumbar facet synovial cyst aspiration technique is a usually safe and minimally invasive procedure. It has good short-term results in terms of pain relief; however, a review of studies utilizing these techniques reveals a high long-term failure rate, which is around 50-100% [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The high-failure rate contributed to failure of complete decompression of these cysts, since they contain thick gelatinous nonabsorbable materials and also it leaves the cyst capsule behind which may still compress the neurological structures leading to lack of complete symptom relief [22].…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde spontan rezorbe olmuş olgular bulunmakla birlikte sıklıkla tedavi gerektirir. [13] Optimal tedavisi konusunda tartışmalar mevcuttur. Tedavisi konservatif ve cerrahi olabilmektedir.…”
Section: Discussionunclassified